2020
DOI: 10.1002/bse.2448
|View full text |Cite
|
Sign up to set email alerts
|

Innovation as a driver of eco‐innovation in the firm: An approach from the dynamic capabilities theory

Abstract: The aim of this study is to investigate how innovative capabilities of the firm affect eco‐innovation from a dynamic capability lens. We build on OECD research to conceptualise eco‐innovation as the capacity with which firms modify, redesign, and create products, processes, procedures, and organisations in order to reduce environmental impact. We propose and test the temporal and relational properties of eco‐innovation as a capability. We demonstrate that eco‐innovation possesses two properties of innovative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 64 publications
7
89
2
5
Order By: Relevance
“…Previous studies have shown a positive correlation between firm R&D investment and green innovation (Arranz, Arroyabe, Li, & Fernandez de Arroyabe, 2020; Liao & Tsai, 2019). We use research and development expenses to measure the firms' overall levels of innovation (Wagner, 2010).…”
Section: Methodsmentioning
confidence: 88%
“…Previous studies have shown a positive correlation between firm R&D investment and green innovation (Arranz, Arroyabe, Li, & Fernandez de Arroyabe, 2020; Liao & Tsai, 2019). We use research and development expenses to measure the firms' overall levels of innovation (Wagner, 2010).…”
Section: Methodsmentioning
confidence: 88%
“…Systems thinking can identify problems within the system and solve the root cause of these problems through a multi-disciplinary "frame" [61]. At present in China, individuals, enterprises, and even the government are advocating technological innovation and system development, which means that future technological innovation presents many challenges [62].…”
Section: The Foundation Of the Pioneering Method: The Link Between Itmentioning
confidence: 99%
“…Systems thinking can identify problems within the system and solve the root cause of these problems through a multi-disciplinary “frame” [ 61 ]. At present in China, individuals, enterprises, and even the government are advocating technological innovation and system development, which means that future technological innovation presents many challenges [ 62 ]. Relying on a simple linear perspective is not sufficient to resolve these challenges; it is also necessary to adopt nonlinear systems thinking and to explore thinking and decision-making from a perspective more in line with the laws of nature [ 63 ].…”
Section: The Foundation Of the Pioneering Method: The Link Between Itmentioning
confidence: 99%
“…Several scholars demonstrated that external and internal knowledge has a significant role in driving eco-innovation strategies (Marzucchi & Montresor, 2017). Other researchers suggested that enterprises' knowledge received from past innovation boosts innovations, in particular, eco-innovation (Arranz, Arroyabe, Li, & de Arroyabe, 2020). It should be noted as well as enterprises' and entrepreneurs' knowledge positively affects the emergence of eco-innovation (Kobarg, Stumpf-Wollersheim, Schlägel, & Welpe, 2020), which is the case of entrepreneurs' PK.…”
Section: Prior Knowledgementioning
confidence: 99%